Mechanisms of algal biomass input enhanced microbial Hg methylation in lake sediments. (May 2019) - Lei, Pei; Nunes, Luís M.; Liu, Yu-Rong; Zhong, Huan; Pan, Ke
Abstract: Eutrophication is a major environmental concern in lake systems, impacting the ecological risks of contaminants and drinking water safety. It has long been believed that eutrophication and thus algal blooms would reduce methylmercury (MeHg) levels in water, as well as MeHg bioaccumulation and trophic transfer (e.g., by growth dilution). In this study, however, we demonstrated that algae settlement and decomposition after algal blooms increased MeHg levels in sediments (54–514% higher), as evidenced by the results from sediments in 10 major lakes in China. These could in turn raise concerns about enhanced trophic transfer of MeHg and deterioration of water quality after algal blooms, especially considering that 9 out of the 10 examined lakes also serve as drinking water sources. The enhanced microbial MeHg production in sediments could be explained by the algal organic matter (AOM)-enhanced abundances of microbial methylators as well as the input of algae-inhabited microbes into sediments, but not Hg speciation in sediments: (1) Several AOM components (e.g., aromatic proteins and soluble microbial by product-like material with generally low molecular weights), rather than the bulk AOM, played key roles in enhancing the abundances of microbial methylators. The copies of Archaea- hgcA methylation genes were 51–397% higher in algae-added sediments; thus, MeHg production was also higher. (2) Input of algal biomass-inhabited microbial methylators contributed to 2–21% of total Archaea- hgcA in the 10 lake sediments with added algal biomass. (3) However, AOM-induced changes in Hg speciation, with implications on Hg availability to microbial methylators, played a minor role in enhancing microbial Hg methylation in sediments as seen in X-ray absorption near edge structure (XANES) data. Our results suggest the need to better understand the biogeochemistry and risks of contaminants in eutrophic lakes, especially during the period of algae settlement and decomposition following algal blooms. Graphical abstract: Unlabelled Image Highlights: Algae settlement and decomposition enhanced net MeHg production in lake sediments. Low molecular weight algal organic matter (AOM) increased the abundances of methylators. Input of algae-inhabited microbes into sediments enhanced microbial MeHg production. AOM-induced changes in Hg speciation played a minor role in Hg methylation.